Effects of baricitinib on radiographic progression of structural joint damage at 1 year in patients with rheumatoid arthritis and an inadequate response to conventional synthetic disease-modifying antirheumatic drugs - van der Heijde, Desirée (RMD Open, 2018)
BACKGROUND: Baricitinib was efficacious in a 24-week phase III study in patients with rheumatoid arthritis (RA) and an inadequate response to conventional synthetic disease-modifying anti rheumatic drugs (DMARDs) (csDMARDs) (RA-BUILD). OBJECTIVES: To evaluate radiographic progression of structural joint damage in RA-BUILD patients over 48 weeks of baricitinib treatment in the long-term extension study, RA-BEYOND. METHODS: In RA-BUILD, patients were randomised to placebo, baricitinib 2 mg or 4 mg once daily, with rescue possible from week 16. Patients completing RA-BUILD and entering RA-BEYOND continued to receive the baricitinib dose received at the end of RA-BUILD. Patients receiving placebo were switched to baricitinib 4 mg in RA-BEYOND. Joint damage was measured using the van der Heijde modified total Sharp score. To account for missing scores and scores obtained after rescue, switch or discontinuation of study drug, data were analysed using (1) linear extrapolation (LE) and (2) observed/last observation carried forward (LOCF). The observed/LOCF method used all available observed data, including after rescue or switch, with patients analysed according to original treatment assignment. RESULTS: Using LE, radiographic progression at 24 and 48 weeks was statistically significantly lower for both baricitinib 2 or 4 mg compared with placebo. Only baricitinib 4 mg demonstrated statistically significant inhibition of progressive radiographic joint damage compared with patients initially randomised to placebo using observed/LOCF at week 48. CONCLUSIONS: Once daily oral baricitinib inhibited radiographic progression of structural joint damage in patients with an inadequate response or intolerance to csDMARDs over 48 weeks. The most robust benefit was seen for the 4 mg dose.